Analisis Pemikiran Koperasi Bung Hatta dan Korelasinya - Nurmala N Sabon; Lamondo Lamondo (IAIN Kendari, 2022)
Mohammad Hatta is called the father of Indonesian cooperatives. It is believed that he has succeeded in providing a form of contribution to the theory of populist economics with an applicative form of cooperatives. When a cooperative or small sector is recognized as one that meets the demands of the Indonesian people. Bung Hatta's thinking is built on solidarity and the idea that each member and supporter will value themselves in their own way. Analyzing these operations can help us understand and deal with economic and moral difficulties. An operation must have both factors described below to qualify as